Incidence and short-term outcome of children with symptomatic presentation of organic acid and fatty acid oxidation disorders in Germany - Klose, Daniela; Kölker, Stefan; Heinrich, Beate; Prietsch, Viola; Mayatepek, Ertan; Kries, Rüdiger von; Hoffmann, Georg F. (Pediatrics, 2002)
Objective. To determine the incidence of symptomatic children with inherited organic acid disorders (OADs) and fatty acid oxidation disorders (FAODs) in Germany. - Methods. An active surveillance of symptomatic children with inherited OADs and FAODs was conducted during a time period of 24 months (1999-2000) in Germany. Monthly inquiries were sent to all Departments of Pediatrics by the German Pediatric Surveillance Unit (ESPED) and quarterly to all specialized metabolic laboratories. Newly diagnosed patients were added to the database, recording clinical and biochemical information via a standardized questionnaire. - Results. Prospective surveillance enrolling 844 575 children identified a total of 57 symptomatic children with newly diagnosed OADs or FAODs in states with conventional neonatal screening, resulting in an estimated cumulative incidence of 1:14 800. The most frequent diagnosis among these children was medium-chain acyl-CoA dehydrogenase deficiency (n = 20). The majority of symptomatic children revealed clinical symptoms during the first year of life (n = 36), frequently presenting with acute metabolic crises (n = 31). Eight children died during these crises. Notably, 47 of the symptomatic children suffered from diseases potentially detectable by expanded neonatal screening programs. This subgroup included 29 children presenting with metabolic crises and 7 of the 8 deaths. - Conclusions. Despite increased clinical awareness of OADs and FAODs, the mortality and morbidity for these children remains high, if they are diagnosed after manifestation of clinical disease. An introduction of nationwide neonatal screening programs would change the focus for organic acid analysis from patients presenting with acute metabolic crises to more chronic clinical presentations, especially the cerebral organic acid disorders.
Gesehen am 22.12.2020